Letter to Jane Tolmach from Donald H. Miller - Donald H. Miller:::::: (1976)
In an April 26, 1976 letter, Donald H. Miller thanked Jane Tolmach for her contribution to his reelection campaign for the Oxnard City Council. He expressed appreciation for her support and stated that he hoped to reflect her views in his efforts to improve Oxnard. Miller emphasized that engaged citizens like her make the democratic system work. He noted that by participating in the election, she had exercised a strong voice in the process. The letter was sent by the Don Miller for City Council Committee, with Elaine Miller serving as treasurer.